Altered Circulating Immune Cell Distribution in Traumatic Spinal Cord Injury Patients in Relation to Clinical Parameters - Fraussen, Judith; Beckers, Lien; van Laake-Geelen, Charlotte C. M.; Depreitere, Bart; Deckers, Jens; Cornips, Erwin M. J.; Peuskens, Dieter; Somers, Veerle (Frontiers in Immunology, 2022)
Following a spinal cord injury (SCI), an inflammatory immune reaction is triggered which results in advanced secondary tissue damage. The systemic post-SCI immune response is poorly understood. This study aimed to extensively analyse the circulating immune cell composition in traumatic SCI patients in relation to clinical parameters. High-dimensional flow cytometry was performed on peripheral blood mononuclear cells of 18 traumatic SCI patients and 18 healthy controls to determine immune cell subsets. SCI blood samples were collected at multiple time points in the (sub)acute (0 days to 3 weeks post-SCI, (s)aSCI) and chronic (6 to >18 weeks post-SCI, cSCI) disease phase. Total and CD4+ T cell frequencies were increased in cSCI patients. Both CD4+ T cells and B cells were shifted towards memory phenotypes in (s)aSCI patients and cSCI patients, respectively. Most profound changes were observed in the B cell compartment. Decreased immunoglobulin (Ig)G+ and increased IgM+ B cell frequencies reflected disease severity, as these correlated with American Spinal Injury Association (ASIA) impairment scale (AIS) scores. Post-SCI B cell responses consisted of an increased frequency of CD74+ cells and CD74 expression level within total B cells and B cell subsets. Findings from this study suggest that post-SCI inflammation is driven by memory immune cell subsets. The increased CD74 expression on post-SCI B cells could suggest the involvement of CD74-related pathways in neuroinflammation following SCI. In addition, the clinical and prognostic value of monitoring circulating IgM+ and IgG+ B cell levels in SCI patients should be further evaluated.